Peran Dan Fungsi Notaris Dalam Pembuatan Kontrak Bagi Hasil Minyak Dan Gas Bumi Di Indonesia - Vonna, Zakia; Rahayu, Sri Walny; Nur, M. (Jurnal Hukum & Pembangunan, 2020)
This article describes contract as one of the essential elements in commercial law, one of which is the oil and gas sector. Therefore, in drafting the contract in the sector, requirements set in prevailing laws and regulation need to be met. In practice, notaries are often involved as public officials in the process of contract drafting in accordance with Article 15 of Law No 2 of 2014 regarding the amendment for Law No 30 of 2004 regarding the Legal Constitution of Notary Public Profession, because they are state officials who are authorized to draft and ratify contracts. This research was aimed at explaining the role of a notary on the drafting and ratification of oil and gas production sharing contract in Indonesia. This research was normative legal research with a legal and philosophical approach, and the method was prescriptive analysis. The technique adopted for the current research was library research by applying the legal material analysis of secondary data.